Analisis Harga Wajar Saham Menggunakan Analisis Fundamental dalam Keputusan Investasi Saham - Fitri Sabiyla Yassarah; Sumarno Manrejo; Bambang Prayogo (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
This study aims to determine the fair price of shares in determining stock investment decisions in state-owned banking issuers listed on the Indonesia Stock Exchange in 2019-2023. This research method uses a qualitative descriptive approach. There are three companies in the study that are the subjects of the study, namely PT Bank Rakyat Indonesia, PT Bank Negara Indonesia, and PT Bank Mandiri. Using fundamental analysis with stock valuation using the price earning ratio (PER) method. The study uses secondary data. The application of fundamental analysis with stock valuation using the price earning ratio (PER) method shows that in 2019, 2021, 2022 and 2023 BBRI, BBNI, and BMRI shares were undervalued (cheap), while in 2020 BBRI and BBNI shares were overvalued (expensive) and BMRI shares were undervalued (cheap).